Eat like the animals : what nature teaches us about the science of healthy eating - Raubenheimer, David, 1960-; Simpson, Stephen J. (Houghton Mifflin Harcourt, 2020)
"What drives the human appetite? Two leading scientists share their cutting-edge research (with an emphasis on the role protein plays) to show how we can gain control over what, when, and how much we eat"--